Social Informatics Third International Conference, SocInfo 2011, Singapore, October 6-8, 2011. Proceedings - Datta, Anwitaman; Shulman, Stuart; Zheng, Baihua; aLin, Shou-De; Sun, Aixin; Lim, Ee-Peng (Springer eBooks., 2011)
This book constitutes the proceedings of the Third International Conference on Social Informatics, SocInfo 2011, held in Singapore in October 2011. The 15 full papers, 8 short papers and 13 posters included in this volume were carefully reviewed and selected from 68 full paper and 13 poster submissions. The papers are organized in topical sections named: network analysis; eGovernance and knowledge management; applications of network analysis; community dynamics; case studies; trust, privacy and security; peer-production.